MEDICAL, PSYCHOLOGICAL AND LEGAL ASPECTS TO SUBSTANTIATE THE CONCEPT OF REHABILITATION FOR MILITARY PERSONNEL – PARTICIPANTS OF THE ANTI-TERRORIST OPERATION - Yanchuk, A.O.; Guliak, O.V.; Tverezovsky, M.V.; Pavelko, I.I.; Bernaz, P.V.; Kuznichenko, S.O. (World of Medicine and Biology, 2020)
The purpose of the work was to substantiate the concept of medical and psychological rehabilitation and legal protection of the military personnel participating in ATO / OOS. The psycho-diagnostic study involved 93 military personnel participating in the ATO / OOS with the mean stay of 12-14 months in the war zone in eastern Ukraine, ranging in age from 20 to 30 years. The results of the study indicate that 53.78% of military participants in the ATO / OOS have certain symptoms of post-stress conditions; partial PTSD was diagnosed in 13.97% of the military; the presence of clinically pronounced disorders of post-stress states is subjectively noted by 19.35% of respondents. Depressive symptoms were recorded in 62.39% of respondents, of which 13.99% were at levels above moderate and high. More than half of the respondents noted the symptoms inherent in post-stress disorders - “invasion” - 59.23% for PTSD and 55.90% for ASD; “Avoidance” - 59.63% with PTSD and 66.27% with ASD; the indicator “Hyperactivation” - 58.21 points for PTSD, and 56.04 for ASD, dissociative symptoms and states of distress and maladaptation - 65.66 points for PTSD and 65.56 for ASD. Given the above, it is necessary to work out at the legislative level the medical-psychological concept of rehabilitation of the military personnel participating in ATO / OOS. Into the program of combat training of military personnel, including commanders of all levels, to introduce a course of the basics of psychological assistance in order to adjust the emotional state by providing self and mutual assistance.
Keywords: medical and psychological rehabilitation; participants in ATO / OOS; post-traumatic stress syndrome; acute stress disorder; screening